2022
DOI: 10.1039/d1ra09412b
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear optical properties of transfer ribonucleic acid (tRNA) thin solid films

Abstract: Optical measurements of one of the vital biological molecules (RNA) in the human body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…RNA also has higher UV radiation resilience 21 23 and chemical stability 24 , 25 making it a more promising candidate for practical thin solid film applications. In our prior report 26 , we experimentally confirmed that additional heat should be supplied to make RNA aqueous solutions which strongly implies that RNA can sustain a higher temperature than DNA. An appropriate viscosity of the liquid precursor is essential in TSF processes to provide uniformity in the film thickness.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…RNA also has higher UV radiation resilience 21 23 and chemical stability 24 , 25 making it a more promising candidate for practical thin solid film applications. In our prior report 26 , we experimentally confirmed that additional heat should be supplied to make RNA aqueous solutions which strongly implies that RNA can sustain a higher temperature than DNA. An appropriate viscosity of the liquid precursor is essential in TSF processes to provide uniformity in the film thickness.…”
Section: Introductionsupporting
confidence: 57%
“…An appropriate viscosity of the liquid precursor is essential in TSF processes to provide uniformity in the film thickness. RNA aqueous solution showed a viscosity 5 , 26 much less than DNA solution for the same concentrations. Therefore, conventional spin-coating processes are expected to obtain RNA TSFs more repeatably than DNA TSFs.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…RNA molecules with proper sequence motifs can self-assemble into a 3D hydrogel polymer network without the addition of any cross-linkers or any external or artificial support [ 291 ]. Films made with tRNA showed linear and nonlinear optical properties, representing a high potential in all-RNA photonic device applications and further applications to temperature sensing and thermo-optic devices [ 292 ].…”
Section: Dna/rna Based Metamaterialsmentioning
confidence: 99%
“…There are still very few applications towards the field of optics where RNA derived from biomass has been used. The tRNA powder processed from wheat germs has been used for the assembly of RNA membranes [ 292 ]. Nanoparticles were also obtained from E. coli tRNA with divalent metal cations, which made it possible to obtain particles ranging in size from several to hundreds nanometers [ 393 ].…”
Section: Dna/rna Based Metamaterialsmentioning
confidence: 99%